Kinetic, spatial, and temporal assessent of overspeed towing with elastic tubing - Frisk, H. L.; Gold, M. E.; Biggs, B. R.; Ebben, W. P. (ISBS Proceedings Archive (Michigan), 2022)
Subjects (N = 15) performed sprints over force platforms in a normal condition and in three overspeed conditions of differing elastic tube stretch length. Kinetic and kinematic data were derived. A 3 x 4 RM ANOVA was used to analyze the results. The horizontal and vertical ground reaction force (GRF), and the ratio of horizontal to vertical GRF did not differ among conditions (p > 0.05). However, ground contact time was 8.3% to 10.4% shorter, time between steps was 1.4% to 2.7% lower, distance between steps was up to 1.2% greater, and velocity was 3.7% higher in some overspeed towing conditions compared to the normal condition (p <= 0.05). Longer tube conditions were more optimal in most cases. Compared to normal running, overspeed towing results in increased sprinting velocity despite no differences in horizontal or vertical kinetics compared to normal running.